The formation of loess ground by the process of loessification: a history of the concept - Smalley, Ian; Obreht, Igor (Geologos, 2018)
Loessification is a process by which a body of non-loess ground is transformed into a body of loess ground. The history of loessification is one of controversy and confrontation, largely because of mutual misunderstandings between geologists and pedologists. Lev S. Berg is the ‘only begetter’ of the theory, first proposed in 1916, and propagated throughout his life. R.J. Russell proposed the same approach to the loess in the Lower Mississippi valley in his famous 1944 paper, which contributed enormously to the study of loess in North America. As understanding of the various processes involved in the formation of loess deposits has developed, a compromise position on loess formation has become possible. The major intrinsic features of loess deposits are the open structure and the collapsibility. It appears that the open structure is caused by aeolian depositional processes and the collapsibility is caused by loessification processes. The compromise was initiated by Marton Pécsi in 1990, He endeavoured to retain a loessification aspect in the study of loess deposits, as the subject appeared to be overwhelmed by the aeolian idea system promoted by geologists; it has been mostly a Central European endeavour. The history of the concept of loessification largely involves (1) its development in Russia, (2) its dissemination and discussion – and attempts at refutation and modification – in the wider world.